The effects of polymer modified asphalt binder incorporating with chemical warm mix additive towards water quality degradation. (10th January 2021) - Rahmad, Suzielah; Md Yusoff, Nur Izzi; Fadzil, Syazwani Mohd; Badri, Khairiah Haji; Arshad, Ahmad Kamil; Widyatmoko, Iswandaru; Rosyidi, Sri Atmaja P.
Abstract: Naturally, asphalt binder has compacting and mixing temperatures higher than 150 °C. Both temperatures can be increased by modifying the pristine penetration grade asphalt binder with polymer. However, the warm-mix asphalt (WMA) technology contributes to lowering of these temperatures even though the possibility of environmental effect cannot be neglected. Air pollution and water contamination are two crucial environmental concerns when it comes to chemical reactions of any materials. This study was conducted to investigate the physical characteristics, thermal analysis, leaching and toxicity of polymer-modified asphalt binder (PMA, PG76) and its performance as the binding agent. Physical tests were carried out to determine the durability, quality and performance of PG76 binder. Thermal analysis via thermogravimetry analysis was carried out to observe the stability of the blending at higher temperature. The results illustrated that even though the PMA is added in combination with WMA as additives, the mixes were stable beyond their mixing and compaction temperatures. The decomposition started at temperature >360 °C and ended at temperature <500 °C for all samples. Wetting and spreading behaviours of the blending are also perceived by contact angle method. Increasing amount of WMA allowed the spreading of water on the surface. The surface was deemed to be hydrophilic or poorly hydrophobic. Leaching Tank Test was carried out to simulate water suspension during heavy rainfall and its influence in leaching traces of heavy metal from asphaltic binders. The tests were carried out at 0.25, 1, 2.25, 4, 9, 16, 36, and 64 days to observe the leaching behaviour of heavy metals and determine the toxicity of the samples. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to detect the presence of heavy metals (Cu, Zn, Ni, Pb, Cr and Fe) and the readings were analysed to Heavy Metal Evaluation index (HEI), Heavy Metal Pollution Index (HPI), Degree of Contamination (Cd ), and Metal Quality Index (MQI). The cumulative values of heavy metals are presented in the form of logarithmic graphs. All indices indicated that all samples did not contribute to heavy metal pollution to the surrounding water resources.